Global and Local Discourses on Climate Change: A Perspective from the Concept of Embeddedness - Rai, Jailab Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2011)
Climate change has been becoming a major order of business of all including researchers and academics. This is known that global, national and local organizations, institutions and even the individuals are partaking into the issues with their own perspectives and skills of negotiations. Despite the series of international efforts and attempts, there are also a series of national concerns, efforts and attempts in combating against the effects of global climate change. This paper is an attempt to draw on the overview of contexts and concerns of international communities for combating global climate change and its discursive influence in national policy discourses. Moreover, the paper attempts to assess the local socio-cultural discourses and dynamics of climate change in relation to global and national discourses. Finally the paper highlights on how global and local climate change knowledge networks and epistemic communities either from political processes or the socio-economic fabrics are interrelated and determinant to each other. Keywords: climate change; discourses; embeddeness; dynamics; global; local DOI: 10.3126/dsaj.v4i0.4518 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.143-180